Discrimination of beef meat according to the level of farming intensification through visible and near infrared spectroscopy data and chemometrics - Annalaura Lopez; Elea Caumette; Rennie C. Eppenstein; Nicolò Amalfitano; Isabelle Legrand; Lynda S. Perkins; Nigel Scollan; Pablo Guarnido-Lopez; Isabelle Constant; Fabien Ferlay-Demiaz; Carmen L. Manuelian; Bruno Martin; et al. (Meat Science, 2026)

Beef quality grading using rapid evaporative ionization mass spectrometry (REIMS) - Yafang Cui; Lynda S. Perkins; Jingjing Liu; Alastair B. Ross; Jingyao Wang; Wenyang Jia; Ezequiel Jorge-Smeding; Alix Neveu; Isabelle Legrand; Marie-Pierre Ellies-Oury; Nigel D. Scollan; Jean-Francois Hocquette (Meat Science, 2026)

Discrimination of beef composition and sensory quality by using rapid Evaporative Ionisation Mass Spectrometry (REIMS) - Jingjing Liu; Nick Birse; Carlos Álvarez; Jiaqi Liu; Isabelle Legrand; Marie-Pierre Ellies-Oury; Dominique Gruffat; Sophie Prache; David Pethick; Nigel Scollan; Jean-Francois Hocquette (Food Chemistry, 2024)

Microbial community dispersal from wheat grains to sourdoughs: A contribution of participatory research - Lucas von Gastrow; Elisa Michel; Judith Legrand; Rémy Amelot; Diego Segond; Stéphane Guezenec; Olivier Rué; Véronique Chable; Isabelle Goldringer; Xavier Dousset; Estelle Serpolay‐Bessoni; Bruno Taupier‐Letage; et al. (Molecular Ecology, 2023)
Understanding microbial dispersal is critical to understand the dynamics and evolution of microbial communities. However, microbial dispersal is difficult to study because of uncertainty about their vectors of migration. This applies to both microbial communities in natural and human‐associated environments. Here, we studied microbial dispersal along the sourdoughs bread‐making chain using a participatory research approach. Sourdough is a naturally fermented mixture of flour and water. It hosts a community of bacteria and yeasts whose origins are only partially known. We analysed the potential of wheat grains and flour to serve as an inoculum for sourdough microbial communities using 16S rDNA and ITS1 metabarcoding. First, in an experiment involving farmers, a miller and bakers, we followed the microbiota from grains to newly initiated and propagated sourdoughs. Second, we compared the microbiota of 46 sourdough samples collected everywhere in France, and of the flour used for their back‐slopping. The core microbiota detected on the seeds, in the flour and in the sourdough was composed mainly of microbes known to be associated with plants and not living in sourdoughs. No sourdough yeast species were detected on grains and flours. Sourdough lactic acid bacteria were rarely found in flour. When they were, they did not have the same amplicon sequence variant (ASV) as found in the corresponding sourdough. However, the low sequencing depth for bacteria in flour did not allow us to draw definitive conclusion. Thus, our results showed that sourdough yeasts did not come from flour, and suggest that neither do sourdough LAB.

French consumer evaluation of eating quality of Angus x Salers beef: Effects of muscle cut, muscle slicing and ageing - Jingjing Liu; Liselotte Pannier; Marie-Pierre Ellies-Oury; Isabelle Legrand; Faustine Noel; Bernard Sepchat; Sophie Prache; David Pethick; Jean-François Hocquette (Meat Science, 2023)

Fixism and conservation science - Alexandre Robert; Colin Fontaine; Simon Veron; Anne‐Christine Monnet; Marine Legrand; Joanne Clavel; Stéphane Chantepie; Denis Couvet; Frédéric Ducarme; Benoît Fontaine; Frédéric Jiguet; Isabelle le Viol; et al. (Conservation Biology, 2017)
The field of biodiversity conservation has recently been criticized as relying on a fixist view of the living world in which existing species constitute at the same time targets of conservation efforts and static states of reference, which is in apparent disagreement with evolutionary dynamics. We reviewed the prominent role of species as conservation units and the common benchmark approach to conservation that aims to use past biodiversity as a reference to conserve current biodiversity. We found that the species approach is justified by the discrepancy between the time scales of macroevolution and human influence and that biodiversity benchmarks are based on reference processes rather than fixed reference states. Overall, we argue that the ethical and theoretical frameworks underlying conservation research are based on macroevolutionary processes, such as extinction dynamics. Current species, phylogenetic, community, and functional conservation approaches constitute short‐term responses to short‐term human effects on these reference processes, and these approaches are consistent with evolutionary principles.

Interference between oculomotor and postural tasks in 7–8-year-old children and adults - Agathe Legrand; Karine Doré Mazars; Christelle Lemoine; Vincent Nougier; Isabelle Olivier (Experimental Brain Research, 2016)

Differing effects of prosaccades and antisaccades on postural stability - Agathe Legrand; Karine Doré Mazars; Julie Lazzareschi; Christelle Lemoine; Isabelle Olivier; Julien Barra; Maria Pia Bucci (Experimental Brain Research, 2013)

Pharmacodynamics and pharmacokinetics of single nasal (5 mg and 10 mg) and oral (50 mg) doses of ephedrine in healthy subjects - Ivan Berlin; Dominique Warot; Guy Aymard; Eric Acquaviva; Mayeule Legrand; Benoît Labarthe; Isabelle Peyron; Bertrand Diquet; Philippe Lechat (European Journal of Clinical Pharmacology, 2001)

Subcellular localization of acidic and basic PR proteins in tobacco mosaic virus-infected tobacco - Isabelle Dore; M. Legrand; B. J. C. Cornelissen; J. F. Bol (Archives of Virology, 1991)